An extensive review on the mushroom world - DIPIKA SINGH; KAZI LAYLA KHALED (International Journal of Pharma and Bio Sciences, 2017)
Mushroom is a macro-fungus with a unique fruiting body. It exhibits a saprophytic mode of nutrition. The body consists of mycelium, volva, stem, gill and cap. They are low in calories, carbohydrates, fats and sodium and high in water and fibre content which makes them a great diet food. The objective of this study is to evaluate the types and uses of different edible and poisonous mushrooms. Evidences prove that beneficial mushrooms help to prevent and treat diseases such as cancer, diabetes, hyperlipidemia, arteriosclerosis, and chronic hepatitis. Some of them may also help in the reduction of tumor growth. Some mushrooms also possess antimicrobial, antiviral, immunostimulatory and anti-allergy properties. In contrast, there are some poisonous mushroom which cause health hazards such as gastrointestinal problems, nausea, vomiting and abdominal pain when ingested. Some of them also exert neurological problems such as vertigo, fatigue, tremor and nystagmus.